Ownership Structures, Executive Compensation and Tax Aggressiveness in Indonesia Mining and Plantation Companies: The Moderating Effect of Audit Quality - Kartadjumena, Eriana; Nuryaman, Nuryaman (International Journal of Economics and Financial Issues, 2024)
This study examines how the ownership structure, executive compensation, and audit quality interact to influence tax aggressiveness in Indonesian mining and plantation companies. The proxy for ownership structures is institutional and family ownership, and the proxy for executive compensation is the total salary of directors per year. Meanwhile, the proxy for tax aggressiveness uses the cash effective tax rate, and audit quality is proxied by the Big Four audit firms. Research data were taken from the 233 annual reports of 47 mining and plantation companies that listed on the Indonesia Stock Exchange during the period 2018–2022. The data were analyzed by a panel data regression technique. The results show that both institutional and family ownership have a significant positive effect on tax aggressiveness. While executive compensation has not influenced tax aggressiveness. Moreover, audit quality has a positive moderating effect on the negative relationship between family ownership and the cash effective tax rate. High-quality auditors can restrain family shareholders’ ability to take aggressive tax positions. However, audit quality could not interact to influence the relationship between institutional ownership or executive compensation and tax aggressiveness.